Life history, distribution and seasonal movements of a threatened South African endemic seabream, Chrysoblephus gibbiceps - Attwood, CG; Dawson, ME; Kerwath, SE; Wilke, C (African journal of marine science, 2019)
The red stumpnose Chrysoblephus gibbiceps (Sparidae) is a South African endemic seabream that has been severely depleted by fishing. A total of 678 C. gibbiceps were sampled by line and trawl fishing for a study of their morphology, age, growth, reproduction and diet. In addition, catch records from three time-periods since 1897 were interrogated for distribution patterns and movement behaviour. The sex ratio was 1.5:1 in favour of males. The length-weight relationship, W = 9.32 × 10 −5 L F 2.811 , indicates hypoallometric growth. The bulbous head of large males is a secondary sexual characteristic. A von Bertalanffy growth model was fitted to age data obtained using otolith analyses: L F = 429.9 × (1 - e −0.113(t - (−3.799) ). The maximum recorded age was 48 years, which is among the highest in seabreams, though the species matures after only 3 years. The gonadosomatic index (GSI) of ripe females (4.5%) was comparatively low, and the two-month-long early-summer spawning season was short compared with that of other sympatric seabreams. The very low GSI of ripe males (1.6%) suggests courtship battles and polygamy. The species feeds over low-profile reefs and consolidated sediments. The principal prey are ophiuroids. Although its trophic level is 3.7, C. gibbiceps has a low-nutrition diet. Historical and current catch data confirm a distribution from Cape Point (southeastern Atlantic) to southern KwaZulu-Natal Province (western Indian Ocean). There is evidence for localised migratory patterns, now partly lost due to severe population depletion. Whereas protogyny and resident behaviour have been suggested as traits that render seabreams vulnerable to fishing pressure, C. gibbiceps is a shoaling gonochorist that has collapsed due to fishing.